Nutrition, physical activity and psychological status during lockdown due to covid-19 - Renu Tyagi; Meenal Dhall; Mary Grace Tungdim; Nilupher; Urvashi Gupta; Kshetrimayum Surmala Devi; Jaisleen Kaur; Anuj Pal Kapoor; Monika Saini; Purnima Dhall; Peteneinuo Rulu; Prerna Bhasin; et al. (Acta Scientiarum. Health Sciences, 2022)
Aim of the present study was to assess physical activity, nutrition and psychological status of the population during lockdown due to covid-19. Online survey was conducted among 534 participants within the age range of 16-78 years using convenient sampling. Participants from varied regions within India and abroad were enrolled for the present study. Volunteered participants were solicited to take part in a survey that has to be carried out by filling an online questionnaire form available to them as a URL link in the invitation through WhatsApp/Messenger. The gathered data has been compiled, coded and cleaned using Microsoft Excel. Analysis has been carried out employing descriptive and inferential statistics in SPSS 17.0. Majority of participants in the studied population showed significant change in their nutrition and physical activity status due to lockdown. Covid-19 lockdown did limit their daily activities. It also had impacted their psychological status. The current investigation accentuates the need to pursue suitable life style for the maintenance of optimum metabolism and physiology. Sticking to more regular timetable of meals, effective management of stress levels and continued physical activity during the quarantine and in all the following phases of living is desirable.